Advances in understanding and intervening in teacher stress and coping: The Coping-Competence-Context Theory. (February 2020) - Herman, Keith C.; Reinke, Wendy M.; Eddy, Colleen L.
Abstract: Teacher stress and burnout are associated with many adverse outcomes for teachers, students, and the educational system. This paper describes the Coping-Competence-Context (3C) Theory of Teacher Stress. The theory is based on empirical research on teacher stress and coping highlighted within this special issue and attempts to more explicitly highlight three critical interconnected pathways to teacher stress development and intervention. The 3C model also highlights why teacher stress is important and should be the topic of future inquiry by showing clear links between teacher stress and adverse student and teacher outcomes. Lastly, this paper provides guidance for leverage points to intervene and describes a future research agenda in three domains: measurement, conceptual, and intervention issues and challenges.